Knowledge and Use of Contraception among Married Women - Yadav, Raj Kumar (Academic Voices: A Multidisciplinary Journal, 2016)
This paper deals with knowledge of contraception, ever use of contraception, current use of contraception, purpose for using contraception, reason for not using contraception, future users of contraception and currently users by background characteristics from the selected respondents. The respondents were 121 married women of Birgunj municipality. The analysis reveals that 94.21 percent of the respondents currently use contraception and rest of them did not continue it. Academic Voices Vol.5 2015: 28-33